2020
DOI: 10.2147/blctt.s262592
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of Age on Survival in CLL Patients Receiving Ibrutinib as Initial Therapy</p>

Abstract: Introduction: Recent randomized trials have demonstrated the efficacy of ibrutinib-based therapy in the treatment of patients with CLL. In Alliance A041202, a higher than expected number of unexplained deaths were reported with front-line ibrutinib in a patient population aged at least 65 years compared to ECOG 1912, which included patients up to 70 years of age. Methods: Therefore, we conducted a retrospective analysis to investigate whether ibrutinib was associated with a greater mortality in older patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This finding is similar to results of many national and international works of literature such as Hasan study in the Kurdistan region-Iraq and Parikh et al study in the USA which all found that younger age CLL patients (age ≤55 years) had significantly longer survival duration than older age CLL patients (age >55 years). On other hand, a multicenter analysis study carried in the USA out by Ujjani et al 37 reported no effect of age on treatment response and survival of CLL patients treated by Ibrutinib, but revealed that elderly age patients died more and earlier than younger age patients. The difference might be due to concentrating on outcome of single treatment agent and not including other treatment types or untreated patients.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is similar to results of many national and international works of literature such as Hasan study in the Kurdistan region-Iraq and Parikh et al study in the USA which all found that younger age CLL patients (age ≤55 years) had significantly longer survival duration than older age CLL patients (age >55 years). On other hand, a multicenter analysis study carried in the USA out by Ujjani et al 37 reported no effect of age on treatment response and survival of CLL patients treated by Ibrutinib, but revealed that elderly age patients died more and earlier than younger age patients. The difference might be due to concentrating on outcome of single treatment agent and not including other treatment types or untreated patients.…”
Section: Discussionmentioning
confidence: 97%